Physiological and biochemical traits regulating preharvest sprouting resistance in rice - Raju, Repudi Shalem; Sahoo, Chittaranjan; Hanjagi, Prashantkumar S; Samal , KC; BN, Devanna; Dash, Manasi; Awaji, Sushma M; Baig, MJ (ORYZA-An International Journal of Rice, 2023)
In cereals, pre-harvest sprouting (PHS) or vivipary is a key physiological and agronomic trait that causes huge economic loss. PHS triggered by typhoons, cyclones, and high relative humidity at the late seed maturation stage is becoming a major threat to rice production in India. To explore the mechanism of PHS in rice, we evaluated 96 rice genotypes for PHS resistance and discovered 12 PHS resistant genotypes. These genotypes were classified into two groups susceptible and resistant, based on their phenotype. From the 96 genotypes, 16 contrasting genotypes were chosen, to unravel the underlying mechanism associated with PHS resistance. The results revealed that resistant genotypes had 0% germination at all the flowering stages (20 to 40 DAF), while susceptible genotypes had 4 to 87.5% germination from 20 to 40 DAF. In terms of pericarp color, 7 out of 8 resistant genotypes had red/pigmented pericarp color while the susceptible genotypes had white/non-pigmented pericarp color. The carotenoid content of leaves and seeds from 20 to 40 DAF was also measured and found to be significantly higher in resistant genotypes than susceptible genotypes. Carotenoids have been demonstrated to increase resistance by assisting in the synthesis of ABA and thereby seed dormancy. The 12 resistant genotypes were examined for germination to decide the duration of dormancy. The duration of dormancy varied in these 12 resistant genotypes varying from 10 days up to 40 days after harvest. These findings suggest that these novel PHS resistant genotypes (PB-68, HT-81, PB-50(1), HT-86, HT-20, Mahulata, PB-285, PB-47, NHN-279, PB-65, PB-259 and Budidhan) may be exploited as donors in the crop improvement programmes to generate PHS resistant genotypes.